Non Bullous Congenital Ichthyosiform Erythroderma - Lita Setyowatie; Iskandar Zulkarnain (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2014)
Background: Non bullous congenital ichthyosiform erythroderma (NBCIE) is an inherited genodermatosis, very rare autosomal recessive inflammatory ichthyosis, chronic, characterized by dryness and scaling. Purpose: To describe the clinical manifestations of NBCIE since it is a rare case, occurs in 1 in 300.000 people. Case: Baby MR 5 month old, Javanese boy, with main complaint white scale and redness patches on almost all of his body since 1.5 month old. Born as collodion baby, then the membrane was slowly thinning and became generalized erythroderma on almost all of his body accompanied with fine white scale, large, thick, plate-like scale only on lower leg. No ectropion and eclabium. No relatives in the pedigree suffer from the same disease. Histopathology examination showed non-bullous congenital ichthyosiform erythroderma. Case management: Emollient after bath and pH balance soap. Conclusions: Diagnosis of NBCIE is established from history taking, clinical features, and histopathology examination. Emollient therapy and pH balance soap will eventually lead to improvement.Key words: non bullous congenital ichthyosiform erythroderma, genodermatosis, collodion baby.